Antecedents of Mobile Shopping Adoption in the Information Age. Issue 1 (February 2020) - Liu, Mengwei; Gong, Feng; Chen, Ziqing; Yang, Limei; Lu, Hui
Abstract: Nowadays, mobile shopping has gradually become a way of people's daily consumption. Based on TAM, this paper constructs a theoretical framework model of influencing factors of consumers' adoption of mobile shopping. Through empirical test, the following conclusions are drawn: (1) subjective norms and performance expectations positively influence perceived ease of use, rather than perceived usefulness; (2) perceived entertainment positively affect both perceived ease of usefulness and perceived ease of use; (3) perceived risk and perceived cost have no significant impact on perceived ease of use and perceived usefulness; (4) perceived ease of use and perceived usefulness positively affect consumers' mobile shopping intention.